Taxing Robots as An Automation Control Policy in The Industrial Revolution Development - Nugraha, Nur Arif (Educoretax, 2021)
The development of industrial revolution in this world has led to massive automation in work areas which can be handled with robots. Therefore, it may result in some potitive and negative consequences. This paper suggests policy ideas on taxing robots to control automation in the industrial revolution development. Using qualitative method with literature reviews, data documentation and data analysis, the author raises some ideas to tax the robot as an automation control policy. This study explores the development of industrial revolution which triggers automation in some administrative and repetitive activities. Then, this paper does not only elaborate scientific journal related to robot tax, challenges, and automation as a result of industrial revolution, but also countries which have implemented this policy, so that taxing robots can be utilized as a policy to control the automation. This research found that there are some opportunities to apply the robot tax to control automation. Furthermore, the author suggested alternatives other than robot tax to deal with automation.